Scrutinization of joule heating and viscous dissipation on mhd flow and melting heat transfer over a stretching sheet - Kumar, K. Ganesh; Gireesha, B. J.; Manjunatha, S. (Zielona Góra: Uniwersytet Zielonogórski)
The present paper deals with an analysis of the combined effect of Joule heating and viscous dissipation on an MHD boundary layer flow and melting heat transfer of a micro polar fluid over a stretching surface. Governing equations of the problem are transformed into a set of coupled nonlinear ordinary differential equations by applying proper transformations and then they are solved numerically using the RKF-45 method. The method is verified by a comparison with the established results with limiting solution. The influence of the various interesting parameters on the flow and heat transfer is analyzed in detail through plotted graphs.
Keywords: Joule heating; viscous dissipation; stretching sheet; micro polar dusty fluid; numerical methods